Spatial distribution of available phosphorus in surface road and trackway surface materials on a sheep farm in Ireland - Fenton, Owen; Daly, Karen; Tuohy, Pat; Cardiff, John; Leach, Simon; Sifundza, Lungile Senteni; Murnane, John (Frontiers in Environmental Science, 2024)
Farm roadway runoff is a high-risk source of pollution when connectivity with waters occurs. Nutrients in this runoff are dominated by fresh animal deposits, but recent dairy and beef farm studies showed that available phosphorus (P) accumulates in roadway surface material and can be lost in runoff. A current knowledge gap is to examine available P concentrations in unsealed roadway and trackway (non-maintained) network of a lowland sheep farm. The present study focused on a 45 ha farm stocked with 544 sheep in south-east Ireland. Ten locations were sampled along with the adjacent fields for available P (i.e., Morgan's P) and ancillary parameters (e.g. pH, total P and heavy metals) in December 2022. The first sampling location was on an aggregate roadway and the other nine were on trackways representing an older aggregate roadway network used by the flock but now covered with soil and grass. Results showed a distinct difference in surface material pH between roadway and trackway locations. Trackways had a pH that mimicked adjacent fields around the agronomic optimum for grassland of ~6.2. All sampling locations had elevated available P concentrations, ranging from 26.3 to 111.0 mg L -1 (mean 62.8 mg L -1 ), similar to the spatial distribution for dairy farms but above those found at beef farms previously studied. The highest available P concentrations were found in roadway and trackway sections adjacent to the farmyard. Other elevated sampling areas were on trackways (87.3 or 97.7 mg P L -1 ) away from the farmyard where sheep are funnelled to pasture, stop to seek shade, urinate and defecate but do not graze. By contrast the average available P concentration for the surrounding fields was 8.4 mg L -1 with a range of 2.7 to 15.9 mg L -1 . Two sampling areas create a critical source area where a high available P source becomes mobilised as runoff during rainfall, discharges into an open drainage ditch, which is then connected to a local stream. Breaking the pathway before runoff enters the ditch is a cheap and effective way of mitigating nutrient losses at these two locations.